2013
DOI: 10.1038/ni0813-876b
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: TGF-β is responsible for NK cell immaturity during ontogeny and increased susceptibility to infection during mouse infancy

Abstract: In the version of this article initially published, a label in Figure 2b and the scale size for Figure 5a were incorrect. The left label under the left image in Figure 2b should be CXCL9 (in red);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…We found that HSD reduced the number of CD27 + CD11b + NK cells in the spleen, which are known to be the most powerful subtype, the reduction of which likely affects overall NK cell function. Subsequently, we used another marker to distinguish between the developmental stages of NK cells and found that the number of mature NK1.1 + CD11b + cells was significantly reduced in the spleen and bone marrow, indicating that HSD inhibits NK cell maturation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…We found that HSD reduced the number of CD27 + CD11b + NK cells in the spleen, which are known to be the most powerful subtype, the reduction of which likely affects overall NK cell function. Subsequently, we used another marker to distinguish between the developmental stages of NK cells and found that the number of mature NK1.1 + CD11b + cells was significantly reduced in the spleen and bone marrow, indicating that HSD inhibits NK cell maturation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%